Mexico's Indigenous communities : their lands and histories, 1500-2010 - Ruiz Medrano, Ethelia (Mesoamerican worlds., 2010)
Presenting an account of Indigenous history in central and southern Mexico from the sixteenth to the twenty-first centuries, this title destroys the notion that Indians were victims of forces beyond their control and have little connection with their ancient past.